Trans Kids : Being Gendered in the Twenty-First Century - Meadow, Tey, 1976- (Book collections on Project MUSE., 2018)
"In the first comprehensive academic treatment of the emerging social, medical, and psychological category of the transgender child, ethnographer Tey Meadow introduces readers to a generation of parents who actively facilitate gender nonconformity in their children. Previous generations of parents sent such children for psychiatric treatment aimed at cure, but today such families call their children new names, allow them to wear whatever clothing their children choose, and even approach the state to alter their children's legal gender. Drawing on sociology, philosophy, psychology, and sexuality studies, Meadow depicts the intricate social processes that shape gender acquisition. Atypical gender expression was once considered a failure of gender, but now it is a form of gender that underscores both the centrality of ever more particular configurations of gender in psychic life and the increasing embeddedness of personal identities in social institutions"--Provided by publisher.